Tembilahan Culinary Area Di Tembilahan Dengan Pendekatan Arsitektur Tropis - Abyadh Nadhiifun; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tembilahan is one of The districts located in Indragiri Hilir regency in Riau Province. The development of The culinary world in The affluent neighborhood Tembilahan city is growing rapidly. Can be seen from many places Tembilahan culinary region are not arranged placement. Tembilahan there are not yet facilities that facilitate activities of the culinary field. Businesses that can be done to meet needs of The community in the culinary world as a means of educational, informative, and this commercial need for a container that meets the needs of the community will have the culinary world in an area which facilitate the public to obtain information and recreation culinary. Tembilahan Culinary Area design, design approach adopted is tropical architecture. And The concept is applied